Treg and Oligoclonal Expansion of Terminal Effector CD8+ T Cell as Key Players in Multiple Myeloma - Joshua, Douglas E.; Vuckovic, Slavica; Favaloro, James; Lau, Ka Hei Aleks; Yang, Shihong; Bryant, Christian E.; Gibson, John; Ho, Phoebe Joy (Frontiers in Immunology, 2021)
The classical paradigm of host-tumor interaction, i.e. elimination, equilibrium, and escape (EEE), is reflected in the clinical behavior of myeloma which progresses from the premalignant condition, Monoclonal Gammopathy of Unknown Significance (MGUS). Despite the role of other immune cells, CD4+ regulatory T cells (Treg) and cytotoxic CD8+ T cells have emerged as the dominant effectors of host control of the myeloma clone. Progression from MGUS to myeloma is associated with alterations in Tregs and terminal effector CD8+ T cells (TTE). These changes involve CD39 and CD69 expression, affecting the adenosine pathway and residency in the bone marrow (BM) microenvironment, together with oligoclonal expansion within CD8+ TTE cells. In this mini-review article, in the context of earlier data, we summarize our recent understanding of Treg involvement in the adenosine pathway, the significance of oligoclonal expansion within CD8+ TTE cells and BM-residency of CD8+ TTE cells in MGUS and newly diagnosed multiple myeloma patients.